Chitosan oligosaccharides attenuate loperamide-induced constipation through regulation of gut microbiota in mice. (1st February 2021) - Zhang, Xiaoyu; Yang, Huabing; Zheng, Junping; Jiang, Nan; Sun, Guangjun; Bao, Xinkun; Lin, Aizhen; Liu, Hongtao
Graphical abstract: Highlights: Chitosan oligosaccharides (COS) attenuated constipation in loperamide-induced mice. COS reshaped the structure of disbalanced gut microbiota in constipated mice. COS regulated production of intestinal metabolites in constipated mice. COS improved constipation through the regulation of gut microbiota in mice. Abstract: This study was designed to explore the improvement of chitosan oligosaccharides (COS) on constipation through regulation of gut microbiota. Here, we proved that COS treatment profoundly boosted intestinal motility, restrained inflammatory responses, improved water-electrolyte metabolism and prevented gut barrier damage in constipated mice induced by loperamide. By 16S rDNA gene sequencing, the disbalanced gut microbiota was observed in constipated mice, while COS treatment statistically reversed the abundance changes of several intestinal bacteria at either phylum, family and genus levels, which partly led to the balance in production of intestinal metabolites including bile acids, short-chain fatty acids and tryptophan catabolites. In addition, COS failed to relieve the constipation in mice with intestinal flora depletion, confirming the essentiality of gut microbiota in COS-initiated prevention against constipation. In summary, COS can ameliorate the development of loperamide-induced constipation in mice by remodeling the structure of gut microbial community.